Exploring the treatment of COVID‐19 with Yinqiao powder based on network pharmacology. (15th January 2021) - Lin, Haixiong; Wang, Xiaotong; Liu, Minyi; Huang, Minling; Shen, Zhen; Feng, Junjie; Yang, Huijun; Li, Zige; Gao, Junyan; Ye, Xiaopeng
Abstract : Coronavirus disease 2019 (COVID‐19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). In China, Yinqiao powder is widely used to prevent and treat COVID‐19 patients with Weifen syndrome. In this study, the screening and verification of active ingredients, target selection and DisGeNET scoring, drug–ingredient–gene network construction, protein–protein interaction network construction, molecular docking and surface plasmon resonance (SPR) analysis, gene ontology (GO) functional analysis, gene tissue analysis, and kyoto encyclopedia of genes and genomes (KEGG) pathway analysis were used to explore the active ingredients, targets, and potential mechanisms of Yinqiao powder in the treatment of COVID‐19. We also predicted the therapeutic effect of Yinqiao powder using TCM anti‐COVID‐19 (TCMATCOV). Yinqiao powder has a certain therapeutic effect on COVID‐19, with an intervention score of 20.16. Hesperetin, eriodictyol, luteolin, quercetin, and naringenin were the potentially effective active ingredients against COVID‐19. The hub‐proteins were interleukin‐6 (IL‐6), mitogen‐activated protein kinase 3 (MAPK3), tumor necrosis factor (TNF), and tumor protein P53 (TP53). The potential mechanisms of Yinqiao powder in the treatment of COVID‐19 are the TNF signaling pathway, T‐cell receptor signaling pathway, Toll‐like receptor signaling pathway, and MAPK signaling pathway. This study provides a new perspective for discovering potential drugs and mechanisms of COVID‐19.